PSIA : Power Sector Reforms and the Poor in Vietnam - Kozel, Valerie (World Bank, Washington, DC, 2017)
Vietnam is implementing a long run reform agenda for the power sector, with the aim of restructuring the sector to improve internal operations, efficiency, and the quality of services. The World Bank has an ongoing engagement in the sector which started in 1995. The design and implementation of the power sector reform strategy has been supported through technical assistance and lending operations, as well as preparation of a proposed series of Power Sector Reform Development Policy Loans (DPLs). A number of Poverty and Social Impact Assessment (PSIA) activities will be carried out in support of Vietnam's power sector reforms and as part of the World Bank's due diligence work for the power sector DPLs. This PSIA focuses on assessing the distributional impacts of recent tariff reforms introduced in March, 2009 which changed Vietnam's Incremental Block Tariff (IBT) structure for residential consumers. In addition to changes in lifeline tariffs and coverage, all on-grid rural consumers were brought under a unified tariff structure.